Surprisingly low compliance to local guidelines for risk factor based screening for gestational diabetes mellitus - A population-based study - Winkvist Anna; Persson Margareta; Mogren Ingrid (BMC, 2009)
Abstract Background Screening for gestational diabetes mellitus (GDM) is routine during pregnancy in many countries in the world. The screening programs are either based on general screening offered to all pregnant women or risk factor based screening stipulated in local clinical guidelines. The aims of this study were to investigate: 1) the compliance with local guidelines of screening for GDM and 2) the outcomes of pregnancy and birth in relation to risk factors of GDM and whether or not exposed to oral glucose tolerance test (OGTT). Methods This study design was a population-based retrospective cross-sectional study of 822 women. A combination of questionnaire data and data collected from medical records was applied. Compliance to the local guidelines of risk factor based screening for GDM was examined and a comparison of outcomes of pregnancy and delivery in relation to risk factor groups for GDM was performed. Results Of the 822 participants, 257 (31.3%) women fulfilled at least one criterion for being exposed to screening for GDM according to the local clinical guidelines. However, only 79 (30.7%) of these women were actually exposed to OGTT and of those correctly exposed for screening, seven women were diagnosed with GDM. Women developing risk factors for GDM during pregnancy had a substantially increased risk of giving birth to an infant with macrosomia. Conclusion Surprisingly low compliance with the local clinical guidelines for screening for GDM during pregnancy was found. Furthermore, the prevalence of the risk factors of GDM in our study was almost doubled compared to previous Swedish studies. Pregnant women developing risk factors of GDM during pregnancy were found to be at substantially increased risk of giving birth to an infant with macrosomia. There is a need of actions improving compliance to the local guidelines.